Comprehensive analysis of the carboxylesterase gene reveals that NtCXE22 regulates axillary bud growth through strigolactone metabolism in tobacco - Wang, Lin; Xie, Xiaodong; Xu, Yalong; Li, Zefeng; Xu, Guoyun; Cheng, Lingtong; Yang, Jun; Li, Lei; Pu, Wenxuan; Cao, Peijian (Frontiers in Plant Science, 2022)
Carboxylesterases (CXE) are a class of hydrolytic enzymes with α/β-folding domains that play a vital role in plant growth, development, stress response, and activation of herbicide-active substances. In this study, 49 Nicotiana tabacum L. CXE genes (NtCXEs) were identified using a sequence homology search. The basic characteristics, phylogenetic evolution, gene structure, subcellular location, promoter cis-elements, and gene expression patterns of the CXE family were systematically analyzed. RNA-seq data and quantitative real-time PCR showed that the expression level of CXEs was associated with various stressors and hormones; gene expression levels were significantly different among the eight tissues examined and at different developmental periods. As a new class of hormones, strigolactones (SLs) are released from the roots of plants and can control the germination of axillary buds.NtCXE7, NtCXE9, NtCXE22, and NtCXE24 were homologous to Arabidopsis SLs hydrolase AtCXE15, and changes in their expression levels were induced by topping and by GR24 (a synthetic analogue of strigolactone). Further examination revealed that NtCXE22-mutant (ntcxe22) plants generated by CRISPR-Cas9 technology had shorter bud outgrowth with lower SLs content. Validation of NtCXE22 was also performed in NtCCD8-OE plants (with fewer axillary buds) and in ntccd8 mutant plants (with more axillary buds). The results suggest that NtCXE22 may act as an efficient SLs hydrolase and affects axillary bud development, thereby providing a feasible method for manipulating endogenous SLs in crops and ornamental plants.